Mapping of oxidative stress in immune response induced by polymer gel based Brucella melitensis vaccine in mice - KUMAR, AMIT; GUPTA, V K; MANDIL, R; VERMA, A K; RAHAL, A; YADAV, S K (The Indian Journal of Animal Sciences, 2018)
Brucella melitensis is an obligate intracellular parasite causing worldwide zoonoses. It has been implicated that oxidative stress induced due to bacterial invasion lead to the niche of Brucella in organs like spleen and lymph nodes. The present study was aimed at evaluating the erythrocytic and tissue specific oxidative stress responses induced by intranasal inoculation of killed Brucella whole cell protein antigen in conjunction with a polymer gel adjuvant for offering protection against live virulent Brucella. The results clearly implicate that both the glutathione mediated nonenzymic antioxidant defense system and catalase play a critical role in intracellular antioxidant defense in vaccinated animals along with maintaining an excellent milieu for inducing an active immune potential. At the same time, the antioxidant defenses in all the vital tissues, viz. liver, kidney, lung and spleen of vaccinated mice were almost at par with the adjuvant inoculated animals. Thus, it may be said that intranasal immunization with polymer gel based Brucella vaccine induces an oxidative stress with negligible signs of inflammatory pathophysiology in all the vital organs and supports the development of significant level of immunogenicity against Brucella challenge.